Konsep Pemikiran Sayyid Qutb tentang Bai’ah: Studi Analisis Tafsir Fi Zilalil Qur’an - Muhammad Roni; Muhammad Anzaikhan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Sayyid Qutb's Concept of Bai'ah: Analytical Study of Tafsir Fi Zilalil Qur'anSayyid Qutb's thought in the political dimension is the concept of bai'ah. Bai'ah is an oath of allegiance to the leader as was often done by the companions of the Prophet Muhammad SAW. This article aims to review Sayyid Qutb's thought on the meaning of bai'ah which describes the promise of allegiance and the difference with the integrity pact. This article belongs to literature research with a qualitative approach. The methodology used is an analytical study of tamatic interpretation of the word 'bai'ah' in the book of Tafseer Fi Zilali Al-Quran. As for the verses of the Qur'an related to bai'ah have been found in Surah Al-Fath: 10, 18, and Surah Al-Mumtahanah: 12. The results of the study conclude two main things, first; Bai’ah initiated by Sayyid Qutb must depart from the right dimension of aqidah (not associating partners with Allah SWT) and be pious by not carrying out various actions prohibited by Him. Second; bai'ah is different from the integrity pact, if the integrity pact is more loyal in terms of work, bai'ah consists more of religious and state loyalty.